2019
DOI: 10.1093/asj/sjz101
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Hyaluronidase With Alteplase as Treatment for Hyaluronic Acid Thrombosis

Abstract: Background Hyaluronic acid fillers are the second-most commonly performed nonsurgical procedure. Arterial thrombosis is their most devastating complication. Recent research shows that along hyaluronic acid thrombi, a platelet/fibrin thrombus forms in the site of injection. This is not addressed by current management protocols, which focus on perivascular hyaluronidase plus adjuvant strategies to increase blood flow. We experimented with an animal model utilizing both hyaluronidase and a throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…This effect appears to be triggered by hemostasis and a direct HA–platelet interaction capable of initiating platelet aggregation [ 216 ]. Several studies in the murine epigastric and femoral artery models have confirmed this effect, in which the formation of an early platelet-rich “white thrombus” within the gel plug subsequently extends beyond the bolus to form a fibrin-rich “red thrombus” ( Figure 17 ) [ 160 , 175 ]. The immediacy of this thrombotic pathway suggests an inflammatory etiology initiated by the HA bolus rather than anoxic endothelial injury.…”
Section: Pathophysiology Of Ha-mediated Vascular Occlusionmentioning
confidence: 95%
See 4 more Smart Citations
“…This effect appears to be triggered by hemostasis and a direct HA–platelet interaction capable of initiating platelet aggregation [ 216 ]. Several studies in the murine epigastric and femoral artery models have confirmed this effect, in which the formation of an early platelet-rich “white thrombus” within the gel plug subsequently extends beyond the bolus to form a fibrin-rich “red thrombus” ( Figure 17 ) [ 160 , 175 ]. The immediacy of this thrombotic pathway suggests an inflammatory etiology initiated by the HA bolus rather than anoxic endothelial injury.…”
Section: Pathophysiology Of Ha-mediated Vascular Occlusionmentioning
confidence: 95%
“…Once the dissemination of intraluminal filler is completed, the resulting distribution of gel fragments determines the extent of the occlusive injury. In several animal and human models of FIVO, this distribution typically consists of proximal intraluminal plugs with distally impacted filler microemboli (1–1000 μm), consistent with type III/IV vaso-dissemination ( Figure 13 ) [ 111 , 174 , 175 ].…”
Section: Pathophysiology Of Ha-mediated Vascular Occlusionmentioning
confidence: 99%
See 3 more Smart Citations